2018
DOI: 10.5603/kp.a2018.0147
|View full text |Cite
|
Sign up to set email alerts
|

Direct Absorb bioresorbable scaffold implantation in acute coronary syndrome

Abstract: Direct Absorb implantation in ACS patients may be feasible in a suitable lesion anatomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Rzeszutko et al, [17] reported the in-hospital outcome of 50 ACS patients who received direct scaffold implantation. NSTEMI represent 62 % of their study population.…”
Section: Discussionmentioning
confidence: 99%
“…Rzeszutko et al, [17] reported the in-hospital outcome of 50 ACS patients who received direct scaffold implantation. NSTEMI represent 62 % of their study population.…”
Section: Discussionmentioning
confidence: 99%
“…In ACS the plaque is soft, therefore it is easy to cross the lesion, and the strut is embedded in the plaque, favouring vascular healing. Furthermore, as revealed in the study of Rzeszutko et al [9], correct expansion of the platform is obtained, minimising the possibility of scaffold thrombosis. However, in stable patients, lesions have fibrocalcic plaques that may prevent correct expansion of the platform despite an aggressive postdilation.…”
mentioning
confidence: 93%
“…Therefore, based on direct BVS implant studies [7][8][9] in the setting of ACS, we can conclude that it is a feasible technique with excellent immediate results. However, it is necessary to confirm whether or not this technique has a negative impact in the long term.…”
mentioning
confidence: 93%
See 1 more Smart Citation